DAKWAH SUFISTIK KH. ABDOEL MADJID MA’ROEF MELALUI TAREKAT WAHIDIYAH Mystical Da’wah of KH Abdoel Madjid Ma’roef Through Wahidiyah Sufism - Arif Muzayin Shofwan (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
There is variety model of dakwah, one of them is mystical dakwah. This model tends to reach spiritual consciousness (ma’rifat) which is sometimes hard to be understood. However, KH.Abdoel Ma’ruf through Wahidiyah Sufism was successfully implemented such mystical dakwah. This writing is based on a library research. Data was analyzed using content analysis by selecting and classifying similar data, then analyzing its content. Findings of this study portray that the mystical dakwah approach done by KH Abdoel Madjid Ma’roef through Wahidiyah Sufism is easily accepted by community. This is because he uses these six practical concepts of ma’rifat; (1) li Allah;(2) bi Allah; (3) li al-Rasul; (4) bi al-Rasul; (5) yukti kulla dzi haqqin haqqah; (6) taqdim al-aham fa alaham tsuma al-anfa’ fa al-anfa’. The Sufism teaching is usually perceived as complicated thing, but it is packed as a practical formula by KH Abdoel Madjid Ma’roef, so that it can encourage people’s spiritual consciousness toward God and Prophet Muhammad.